ANALYSIS OF THE EFFECT OF PENSTOCK DIAMETER ON HYDROCOIL TURBINE PERFORMANCE IN SUKAJAYA VILLAGE, LEMBANG DISTRICT, WEST JAVA - alif, irfan alif; Biantoro, Agung Wahyudi (Universitas Mercu Buana, 2025)
The turbine used in this study is a reaction turbine called hydrocoil turbine. In hydrocoil turbines require penstock pipe components to support turbine performance, the size of the penstock pipe has its own potential. Errors in determining the diameter of the penstock can affect the performance of hydrocoil turbines. The purpose of this study is to perform penstock comparison using ansys with a diameter of 6 inches, 8 inches and 10 inches and determine the diameter of the penstock to get the best hydrocoil turbine performance. This study was conducted using Computational fluid dynamics (CFD) method which includes torque, turbine power, and efficiency, the results of the analysis of the calculation of the highest torque value obtained by the 10-inch penstock at 150 rpm rotation of 398.51 Nm, and the torque value obtained by the 8-inch penstock at 150 rpm rotation of 282.47 Nm, the lowest torque value obtained by the 6-inch penstock at 950 rpm rotation of 51,061 Nm. Then the highest power value obtained by the 10-inch penstock at 950 rpm rotation of 27279.53 Watts and the power obtained by the 8-inch penstock at 950 rpm rotation of 21861.41 Watts, the lowest power obtained by the 6-inch penstock at 950 rpm rotation of 5077.16 Watts. So that the highest efficiency value obtained by 10-inch penstock at 950 rpm rotation of 90.58% and the efficiency value obtained by 8-inch penstock at 950 rpm rotation of 72.59 %, the lowest efficiency value obtained by 6-inch penstock at 950 rpm rotation of 16.85 %. It can be concluded from the values already obtained, penstock with a diameter of 10 inches has the highest value to get the best turbine performance, followed by penstock diameter of 8 inches has the highest value Number 2 and penstock with a size of 6 inches has the lowest value, proven by the speed varied according to the diameter of the penstock and constant discharge indicates that the larger the diameter of the penstock will produce the best turbine performance.